Problems with Using Indonesian in Digital Communication and Public Spaces - Azky Abdilah (Jurnal Hata Poda, 2025)
The use of Indonesian in online communication and public spaces is increasingly changing due to the impact of globalization, technological advances, and societal language habits. The purpose of this study is to identify and explain various forms of deviation in the use of Indonesian in various communication contexts, both spoken and written. The method used was observation with a descriptive qualitative approach. The results of the observations revealed various linguistic problems, such as spelling and punctuation errors, inappropriate sentence structure, non-standard word choice, code-mixing and code-switching, ambiguous or illogical sentences, and language deviations in public spaces such as banners and social media. Several influencing factors include informal communication habits, a lack of awareness of proper and correct language, and the dominance of foreign and regional languages in everyday interactions. These findings demonstrate the importance of improving linguistic literacy in society to maintain the function of Indonesian as a language of unity and national identity, especially in the ever-evolving digital era.